PERSEPSI KEPUASAN PASIEN RAWAT JALAN TERHADAP PELAYANAN PETUGAS DI BAGIAN PENDAFTARAN PADA PUSKESMAS SEMATANG BORANG PALEMBANG - Tutik Pebrianti; Sri Porwani (Jurnal Ilmiah Ekonomi Global Masa Kini)
This research was conducted to find out the Perception of outpatient satisfaction to service officersin registration sectionat Puskesmas Sematang Borang Palembang.Data collecting was conducting by using questionnaire instruments in form of questions. The result of this research showed that: satisfaction of outpatient to service of lowest registration officer that  is a statementof charge equal to 66,67%. The perception is most dominant from the outpatient satisfaction  to service officers in registration section that is a statement of service officers in registration section with a courtesy of 81,67%. Keywords: Perseption, Outpatient Satisfaction, Service.